Fantsuam Foundation (Nigeria) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Fantsuam Foundation has adopted an innovative approach to improving healthcare and education, primarily for women, through shared access to ICT facilities.